128k views
3 votes
The equation below was solved incorrectly. Study the work below. 5 = -3(x - 1) Step 1: 5= -3x + 3 Step 2: 2x= 3 Step 3: x = 3/2 1. Describe the mistake in the work shown above.

User Chefhose
by
5.6k points

2 Answers

3 votes

Answer:Step 2 is incorrect because -3x would go to the left side by adding it. Example: 3x=3-5

Which would equal to 3x=-2

Then theanswer would be x=-2/3

User Arise
by
5.9k points
1 vote

Answer:

Explanation:

X= -2/3

User Bongeh
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.